Influence of crystalline boron powders on superconducting properties of C-doped internal Mg diffusion processed MgB2 wires. (3rd September 2015) - Wang, Dongliang; Zhang, Xianping; Tang, Shaopu; Xu, Da; Yao, Chao; Dong, Chiheng; Xu, Zhongtang; Ma, Yanwei; Oguro, Hidetoshi; Awaji, Satoshi; Watanabe, Kazuo
Abstract: Monofilament MgB2 /Fe wires or tapes were fabricated with two different purity crystalline boron powders, using internal magnesium diffusion (IMD) and in situ powder-in-tube (PIT) processes. To evaluate which method was more insensitive to the purity of the boron powders, a sensitivity factor was used. It was found that the IMD process was less sensitive to the purity of the boron powders, compared to the PIT method. Furthermore, J c values of the IMD-processed wires were higher than those of the PIT-processed samples. The reduced porosity and hence the increased density in the IMD-processed samples was thought to be the main reason. Although a number of B-rich particles remained in the MgB2 region, a layer J c as high as 4.8 × 10 4 A cm −2 at 4.2 K and 10 T was still obtained in the IMD-processed wire, which was comparable to that of IMD-processed wires fabricated using amorphous boron powders.